Three‐dimensional regional displacement after surgical–orthodontic correction of Class III malocclusion. (1st November 2015) - Koerich, L.; Ruellas, A. C. O.; Paniagua, B.; Styner, M.; Turvey, T.; Cevidanes, L. H. S.
Structured Abstract: Objectives: To investigate how displacements of maxillo‐mandibular structures are associated with each other at splint removal and 1 year post‐surgery following 1‐jaw and 2‐jaw surgeries for correction of Class III malocclusion. Setting and Sample Population: Fifty patients who underwent surgical correction with maxillary advancement only (n = 25) or combined with mandibular setback (n = 25) were prospectively enrolled in this study. Methods: Cone‐beam computed tomographies were taken pre‐surgery, at splint removal and at 1 year post‐surgery. Three‐dimensional cranial base superimpositions and shape correspondence were used to measure the outcomes from pre‐surgery to splint removal (surgical changes) and splint removal to 1 year post‐surgery (post‐surgical adaptations). Pearson's correlation coefficients were used to evaluate the association between the regional displacements. Results: Both surgery groups presented mandibular clockwise rotation with surgery and post‐surgical adaptive counterclockwise rotation. In patients treated with maxillary advancement only, the surgical changes of the maxilla were significantly correlated with chin changes. The amount and direction of chin autorotation were significantly correlated with right and left ramus autorotation. Right and left condylar displacements were significantly correlated. One year post‐surgery, adaptive displacements and bone remodeling of both rami were correlated with the chin and condylar changes. For the 2‐jaw group, the few correlations between the positional and remodeling changes in the anatomic regions of interest observed due to the surgery were different than those observed after post‐surgical adaptations, suggesting that these changes occurred independently. Conclusion: Our results indicate that surgical displacements and post‐surgical adaptations are often correlated in one‐jaw surgery and are, in general, independent in two‐jaw surgery.